THE SELECTION OF RESERVED STRUCTURE AND THE CREATION OF THE FUNCTION FOR RELIABILITY (Academic journal Industrial Machine Building Civil Engineering, 2017)
The determining of reliability of water systems is introduced, is derived formulas fordefinition the reliability of some water pipe structures and is made the comparative analysis ofreliability and topology of these structures. The engineering method of analysis the reliabilityof tracing the cyclical water pipe systems is developed, which is allowed to select a structure ofnetwork with maximum reliability, is defined the limit reliability of area of network, isidentified that areas which would increase the reliability of the structure during itsdevelopment. The method of graph–analytic formation of tracing the new circular water pipesystem was developed ed, which would given the opportunity to build a number of competitiveoptions for trace circular water network and choose the best for reliability.Keywords: the reliability of the network structure, the topology, the boundary reliabilityof sections.